A Study of Intellectual Property Right on Micro Small and Medium Enterprises: Case Study TanjungBumi Batik - Maya, Siska; Wulandari, Siswi; Purnamasari, Indah (Journal of Economic Development, Environment and People, 2019)
The contribution of Batik industry have exceptional influence for the Indonesian economy. The value of batik and batik products in 2017 reached 58, 46 million us dollars. Indonesian batik is exported to Japan, United State of America, and Europe (Cabinet Secretary Republic Of Indonesia, 2018). In giving incentive towards creativity and innovation to the batik industry, the government have an important role as a regulator. This research used qualitative and investigation method. The local government as a stakeholder or extension of central government play an active role in solving the problems ofintellectual property right especially in batik industry. This will be an incentive for the batik creativity and innovation in the long term.